New Mediterranean Biodiversity Records (October 2015) - F. CROCETTA; D. AGIUS; P. BALISTRERI; M. BARICHE; Y.K. BAYHAN; M. ÇAKIR; S. CIRIACO; M. CORSINI-FOKA; A. DEIDUN; R. EL ZRELLI; D. ERGÜDEN; J. EVANS; et al. (Mediterranean Marine Science, 2015)
The Collective Article “New Mediterranean Biodiversity Records” of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided per countries, listed according to a Mediterranean west-east geographic position. New biodiversity data are reported for 7 different countries, although one species hereby reported from Malta is overall new for the entire Mediterranean basin, and is presumably present also in Israel and Lebanon (see below in Malta). Italy: the rare native fish Gobius kolombatovici is first reported from the Ionian Sea, whilst the alien jellyfish Rhopilema nomadica and the alien fish Oplegnathus fasciatus are first reported from the entire country. The presence of O. fasciatus from Trieste is concomitantly the first for the entire Adriatic Sea. Finally, the alien bivalve Arcuatula senhousia is hereby first reported from Campania (Tyrrhenian Sea). Tunisia: a bloom of the alien crab Portunus segnis is first reported from the Gulf of Gabes, from where it was considered as casual. Malta: the alien flatworm Maritigrella fuscopunctata is first recorded from the Mediterranean Sea on the basis of 25 specimens. At the same time, web researches held possible unpublished records from Israel and Lebanon. The alien crab P. segnis, already mentioned above, is first formally reported from Malta based on specimens collected in 1972. Concomitantly, the presence of Callinectes sapidus in Maltese waters is excluded since based on misidentifications. Greece: the Atlantic northern brown shrimp Penaeus atzecus, previously known from the Ionian Sea from sporadic records only, is now well established in Greek and international Ionian waters. The alien sea urchin Diadema setosum is reported from the second time from Greece, and its first record date from the country is backdated to 2010 in Rhodes Island. The alien lionfish Pterois miles is first reported from Greece and concomitantly from the entire Aegean Sea. Turkey: the alien rhodophyte Antithamnion hubbsii is first recorded from Turkey and the entire eastern Mediterranean. New distributional data are also offered for the native fishes Alectis alexandrina and Heptranchias perlo. In particular, the former record is constituted by a juvenile of 21.38 mm total length, whilst the latter by a mature male. Cyprus: the rare native cephalopod Macrotritopus defilippi, and the alien crab Atergatis roseus, sea slug Plocamopherus ocellatus and fish Cheilodipterus novemstriatus are first recorded from the entire country. Lebanon: the alien crabs Actaea savignii and Matuta victor, as well as the alien fish Synanceia verrucosa, are first recorded from the entire country. In addition, the first Mediterranean record of A. savignii is backdated to 2006, whilst the high number of M. victor specimens observed in Lebanon first suggest its establishment in the basin. The Atlantic fishes Paranthias furcifer and Seriola fasciata, and the circumtropical Rachycentron canadum, are also first reported from the country. P. furcifer record backdate its presence in the Mediterranean to 2007, whilst S. fasciata records backdate its presence in the eastern Mediterranean to 2005. Finally, two of these latter species have been recently ascribed to alien species, but all the three species may better fit the cryptogenic category, if not a new one.